Prospective Study Examining the Effects of Extreme Drinking on Brain Structure in Emerging Adults. (24th September 2020) - Hua, Jessica P. Y.; Sher, Kenneth J.; Boness, Cassandra L.; Trela, Constantine J.; McDowell, Yoanna E.; Merrill, Anne M.; Piasecki, Thomas M.; Kerns, John G.
Abstract : Background: Emerging adulthood is a critical neurodevelopment period in which extreme drinking has a potentially pronounced neurotoxic effect. Therefore, extreme drinking, even a single episode, could be particularly harmful to the developing brain's structure. Relatedly, heavy alcohol use in emerging adults has been associated with structural brain damage, especially in the corpus callosum. However, it is unclear whether and how much a single extreme drinking episode would affect brain morphometry. Methods: For the first time in the literature, the current study prospectively examined the impact of an extreme drinking episode (i.e., twenty‐first birthday celebration) on the brain morphometry of emerging adults immediately following their birthday celebration ( n = 50) and approximately 5 weeks post–birthday celebration ( n = 29). Results: We found evidence that a single extreme drinking episode was associated with structural changes immediately post–birthday celebration. Specifically, higher twenty‐first birthday estimated blood‐alcohol concentration was associated with decreased volume of the posterior and central corpus callosum immediately post–birthday celebration. This extreme drinking episode was not associated with further structural changes, or recovery, 5 weeks post–twenty‐first birthday celebration. Conclusions: Overall, results suggest that a single episode of heavy drinking in emerging adulthood may be associated with immediate structural changes of the corpus callosum. Thus, emerging adulthood, which is characterized by high rates of extreme drinking, could be a critical period for targeted prevention and intervention. Abstract : Participants were scanned prior to and a few days after their 21st birthday celebration. Higher estimated blood‐alcohol concentration (eBAC) on the 21st birthday was associated with decreased volume of the posterior corpus callosum at the scan given post‐21st birthday celebration. Results suggest that a single episode of heavy drinking in emerging adulthood may be associated with immediate structural changes of the corpus callosum.